Strategi Pemasaran Islam dalam Meningkatkan Minat Nasabah pada Produk Pembiayaan Mudharabah di BMT Surya Kencana Jambon Ponorogo - Dwinata, Danti; Arifah, Khoirul; Taufiqurrahman, Rizal; Albanjari, Fatkhur Rohman (Musyarakah: Journal of Sharia Economic (MJSE), 2025)
The purpose of this to examine the Islamic-based marketing strategies used by BMT Surya Kencana Jambon in increasing customer interest in Mudharabah financing products. Mudharabah financing is a form of cooperation between investors (shahibul maal) and business actors (mudharib) with a profit-sharing system based on sharia principles. This study employs a descriptive qualitative method with an observational approach, interviews, and documentation. The results of the study indicate that marketing strategies are implemented through two approaches, namely offline (distribution of brochures, personal approaches, and business assistance) and online (use of Facebook and WhatsApp Business applications). Marketing is carried out based on Islamic principles such as shiddiq, amanah, tabligh, and fathanah. Although these strategies have successfully attracted customer interest, BMT still faces several challenges, such as low public understanding of Islamic finance, limited human resources, and intense competition with other financial institutions. Therefore, improving financial literacy, developing human resource quality, and implementing technology are crucial factors to ensure the sustainability of ethical Mudharabah financing marketing based on Islamic values.